Principles and Protocols For Post-Cryopreservation Quality Evaluation of Stem Cells in Novel Biomedicine - Xie, Jingxian; Ekpo, Marlene Davis; Xiao, Jian; Zhao, Hongbin; Bai, Xiaoyong; Liang, Yijie; Zhao, Guang; Liu, Dong; Tan, Songwen (Frontiers in Pharmacology, 2022)
In recent years, stem cell therapy has become a very promising and advanced scientific research topic. The storage and transportation of stem cells limit the clinical application. Cryopreservation technology makes it possible for living tissues, cells and even living organisms to survive for a long time at deep low temperatures. Stem cell preparations are subject to three major damages: osmotic damage, mechanical damage, and peroxidative damage during cryopreservation. Assessing the effectiveness and safety of stem cells following cryopreservation is fundamental to the quality control of stem cell preparations. Here, we discuss biosafety and quality analysis considerations for manufacturing clinical grade cell products for successful clinical application, and provide a reference for protocol in the quality control of stem cell preparations.